2015
DOI: 10.5223/pghn.2015.18.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Wilson's Disease in Bangladeshi Children: Analysis of 100 Cases

Abstract: PurposeTo evaluate clinical and laboratory profile of Wilson's disease (WD) in children.MethodsThis cross sectional study was conducted at Bangabandhu Sheikh Mujib Medical University Hospital. Bangladesh, over a period of 3 years. One hundred consecutive children of WD between 3 to 18 years of age were evaluated.ResultsMean age was 8.5±1.5 years. Male female ratio was 2:1. Ninety-one percent of patients were Muslim and 9% Hindu. A total of 53% cases of hepatic WD presented between 5 to 10 years of age and most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 29 publications
5
58
2
4
Order By: Relevance
“…Observation of KF ring more frequently in patients with neurological findings may be related with the fact that neurological findings emerge at more advanced ages. In previous studies, the frequency of KF ring in children with WD was reported to range between 38% and 76% (7,12). KF ring was found in 50% of the patients included in this study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Observation of KF ring more frequently in patients with neurological findings may be related with the fact that neurological findings emerge at more advanced ages. In previous studies, the frequency of KF ring in children with WD was reported to range between 38% and 76% (7,12). KF ring was found in 50% of the patients included in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Although patients generally present with clinical findings related with hepatic dysfunction, patients without a diagnosis of WD who had presented only with neurological findings have been reported (7). In this study, three (25%) of our patients presented to our clinic with neurological findings and were diagnosed with WD as a result of systemic investigations.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although the diagnosis of WD is made in the first decade of life in children, the neurological symptoms of WD are mostly observed in second decade [6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 100 cases of WD in children, there were 69 children with hepatic presentation only, 14 children with both hepatic/neurological presentation, 11 asymptomatic children (diagnosed on family screening) and 6 children with neurological presentation only (5 children >10 years old) 13. However, looking specifically at children with neurological presentation of WD only, two different case series reports from Pakistan and Italy demonstrated 46/50 children and 2/6 children, respectively, with normal transaminases at presentation 4 14.…”
Section: Indications and Limitationsmentioning
confidence: 99%